Novel use of the Heald anal stent after transanal endoscopic microsurgery - Alun E. Jones; Guy F. Nash (Surgical Techniques Development, 2011)
Distension of the rectum following transanal endoscopic microsurgery (TEMS) increases rectal intra-luminal pressure and may promote pelvic sepsis by contaminating the rectal defect. We describe the first use of a Heald anal stent to decompress the rectum following TEMS. Transanal endoscopic microsurgery (TEMS) is an increasingly popular method of resecting rectal neoplasms with minimal morbidity and mortality. Following excision of the lesion, the defect in the rectal wall is usually repaired by a continuous suture. However there is no evidence to suggest defect closure is superior to leaving this to heal by secondary intention. Distension of the rectum post-operatively increases rectal intra-luminal pressure and may promote pelvic sepsis by contaminating the rectal defect.